Enterprise-wide risk management best practices: The critical success factors - Ab. Wahab, Norlida; Othman, Siti Norezam; Kasim, Isahak (Ontario International Development Agency, 2012)
This paper examines the critical success factors of effective Enterprise-Wide Risk Management (EWRM) practices that have an effect on shareholder value. Financial and non-financial companies of Public Listed Companies (PLCs) of service sector had been chosen as a population to determine the crucial factors that should be considered for a success implementation of EWRM. A triangulation approach was adopted to get an enriched data collection and analysis for the study.From a survey on 14 financial companies and 41 non financial companies and 4 companies of a case study, it is found that organisational culture is a most critical factor which contributes more to a success implementation of EWRM and has an effect on shareholder value. Significantly, the function and the effectiveness of other critical success factors were depended on strong organisational culture. The other EWRM critical success factors identified were risk management base, compliance, resource, cross functional staff, knowledge management, and authority or power.